Remediação in vitro de poluentes orgânicos persistentes com utilização de plantas e nanopartículas - Almeida, Marcos Vinícius de (2013)
Environmental pollution has been a complex problem which generates a lot of ecological consequences. Among all chemicals produced by anthropic activity human, there isa wide range of organic compounds affecting on the environment and human health, which were grouped under the acronym POPs, Persistent Organic Pollutants. These compounds have been targeted at all conventions on the global environment. Bioremediation, phytoremediation and thermal treatment are techniques that have been tested in recent years and in many cases showed good results for decontamination matrices such as soil and water. Nanotechnology emerged in the recent years as an important tool for environmental purification and has been highly used by presenting itself as technological option for "green oxidation". Plants can also be considered as component of aggregation and transformation of organic compounds in their tissues and can also be applied in phytoremediation purposes both in vivo and in vitro models. This study developed a remediation method fully in vitro, in contrast to traditional methods in vivo. Two novel protocols were established by the development of in vitro culture: one for bamboo species Bambusa vulgaris var. vitatta and other for sunflower Helianthus annuus. L. The study of bioremediation effects of these species in vitros howed promising results for seventeen from twenty-four compounds evaluated using sunflower reaching until 87% for remediation. Moreover, it was possible to verify the nanostructured TiO2 toxicity to the studied species at different stages of development. The use of nanostructured TiO2 in the remediation of aqueous samples contaminated with POPs showed promising results in degradation of around 50% for most pollutants. This work suggests an interesting comparison of the potential of these techniques in environmental applications with respect to efficiency, practicality and toxicity especially focus in go remediation processes certainly due to its dynamic results can provide environmentally attractive and can even be used together.